Pengembangan Digitalisasi Koperasi Dan UMKM Kota Malang Dalam Pengembangan Produk Tingkat Nasional - WIASTONO, AGUS; KOSLANI, (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
The purpose of this study is to uncover the challenges and opportunities, especially digitalization in various economic aspects such as in cooperatives. This study aims to analyze whether the implementation of digital cooperatives is in accordance with the principles or concepts of digitalization. This study uses a descriptive approach to understand the situation. Participants in this study involved one of the cooperatives in Malang Regency, which has been engaged in production cooperatives with various types of business and has used digital in the implementation process. The data in this study use primary and secondary data obtained directly through interviews and literature studies. The results of this study are expected to provide an overview and input on how to implement appropriate digital cooperatives as a step in efforts to empower cooperatives in the digital era.